2008
DOI: 10.1137/070691322
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Expansions of I-V Relations via a Poisson–Nernst–Planck System

Abstract: Abstract. We investigate higher order matched asymptotic expansions of a steady-state Poisson-Nernst-Planck (PNP) system with particular attention to the I-V relations of ion channels. Assuming that the Debye length is small relative to the diameter of the narrow channel, the PNP system can be viewed as a singularly perturbed system. Special structures of the zeroth order inner and outer systems make it possible to provide an explicit derivation of higher order terms in the asymptotic expansions. For the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 47 publications
0
85
0
Order By: Relevance
“…Numerical studies have shown that classical PNP models provide good qualitative agreement with experimental data for I-V relations [4,5]. Dynamics of classical PNP models has also been analyzed by using asymptotic expansion methods [1,6,32,42,49,50,52,55] and geometric singular perturbation approaches [14,15,35,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies have shown that classical PNP models provide good qualitative agreement with experimental data for I-V relations [4,5]. Dynamics of classical PNP models has also been analyzed by using asymptotic expansion methods [1,6,32,42,49,50,52,55] and geometric singular perturbation approaches [14,15,35,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…. ,m. In the first stage over [x 0 , x 1 ] = [0, x 1 ], it will start near the point (ν 0 , u [0] , L, J * , x 0 ), follow the singular layer Γ [0,r] toward the slow manifold Z 1 , move along the regular layer Λ 1 , and leave the vicinity of Z 1 along the singular layer Γ [1,l] toward the point (φ [1,l] , u [1] , C [1,l] , J * , x 1 ). It then continues the evolution over each subsequent sub-intervals in a similar fashion until it reaches the vicinity of the…”
Section: Transversality and Validation Of Singular Orbitsmentioning
confidence: 99%
“…The electric field is strong throughout these systems and only a few charges (ions) are needed to create significant electrical potentials, compared to the enormous number of ions (10 23 , Avogadro's number) needed to create chemical potentials (and diffusion). That is why the Debye number is so large (see system (1)). The flow through the atomic scale channel is affected by other variables besides the applied boundary potentials in the reservoirs, namely, by the shape of the pore in the channel (through which permanently charged ions flow) and the distribution of permanent and induced (i.e., polarization) charge on the wall of the channel as well as the mobility of ions [13,21,27,28,34,40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We use a modified PNP formulation to account for the presence of steric effects [52][53][54], which are shown to play a prominent role in shaping the charge distribution in the composite layers at moderately large voltages, see also the comprehensive review in [55]. Following [37,40,[52][53][54][56][57][58][59][60], we use the method of matched asymptotic expansions, see for example [61], to derive a semi-analytical solution for the electric potential and the charge concentration in the IPMC along with a new circuit model for IPMCs in presence of a DC voltage bias. The equivalent circuit model consists of the series connection of two impedances of the form presented in [24] to account for differences in charge build up at the anode and cathode regions for large voltages.…”
Section: Introductionmentioning
confidence: 99%